Akuntansi dalam Rumah Tangga : Study Fenomenologi pada Akuntan dan Non Akuntan - Melia Yulianti; Hidayatul Ihsan; Eliyanora (Akuntansi dan Manajemen, 2016)
Some people or couples in the household who are responsible for household finances. This research was conducted by comparing qualitative in accounting aspects investigated by motivation, benefits and values ​​developed in household accounting practices as well as budgeting, recording, decision making and long-term financial planning. Data was collected through semi structured interview collection. As informants who were made the object of this study were household partners who work as accountants and non accountants. Furthermore, the research findings were analyzed by discussing the theme, with mental accounting as the theoretical agreement. The results of the study show how accounting practices in the families of accountant and non-accountant families vary where not only the background of education but also related to employment, non-geographical and mental status needed by couples in practicing accounting in the household. for household partners in managing household finances.